A microbiological assay to estimate the antimicrobial activity of parenteral tildipirosin against foodborne pathogens and commensals in the colon of beef cattle and pigs. Issue 3 (5th November 2015) - Rose, M.; Pridmore, A.; Shaw, A.; Wilhelm, C.; Menge, M.; Kilp, S.; Röpke, R.; Nürnberger, M.
Abstract : Tildipirosin (TIP) is a novel 16‐membered‐ring macrolide authorized for the treatment of bovine and swine respiratory disease. The pH dependency of macrolide antimicrobial activity is well known. Considering that the pH in the colon contents of growing beef cattle and pigs is usually below pH 7.0, the minimum inhibitory concentrations (MIC) of TIP against foodborne bacterial pathogens such as Campylobacter (C.) coli, C. jejuni and Salmonella enterica and commensal species including Enterococcus (E.) faecalis, E. faecium and Escherichia coli were determined under standard (pH 7.3 ± 1) or neutral as well as slightly acidic conditions. A decrease in pH from 7.3 to 6.7 resulted in an increase in MICs of TIP. Except for the MICs > 256  μ g/mL observed in the resistant subpopulation of the C. coli and the Enterococcus species, the MIC ranges increased from 2–8  μ g/mL to 64–> 256  μ g/mL for Salmonella enterica and E. coli, from 8–16  μ g/mL to 32–128  μ g/mL for the two Campylobacter species, and from 4–32  μ g/mL to 128–> 256  μ g/mL for both Enterococcus species. To estimate the antimicrobial activity of TIP in the colon contents of livestock during recommended usage of the parenterally administered TIP (Zuprevo ® ), and to compare this with the increased MICs at the slightly acidic colonic pH, we developed and validated a microbiological assay for TIP and used this to test incurred faecal samples collected from cattle and pigs. Microbiological activity of luminal TIP was determined in aqueous supernatants from diluted faeces, using standard curves produced from TIP‐spiked faecal supernatants. The limit of quantification (LOQ) for TIP was 1  μ g/mL (ppm). In a cattle study ( n  = 14), 3 of 28 faecal samples collected 24 and 48 h post‐treatment were found to contain TIP above the LOQ (concentrations of 1.3–1.8 ppm). In another cattle study ( n  = 12) with faecal samples collected at 8, 24 and 48 h post‐treatment, TIP concentrations were above the LOQ in 4 of the 8 h samples (1.2–2.6 ppm) and one of the 24‐h samples (1.3 ppm). In a pig study ( n  = 12) with faecal samples collected 24, 48 and 72 h post‐treatment, only one sample contained TIP above the LOQ (concentration 1.5 ppm). In another pig study ( n  = 12), with samples collected at 8, 24 48 and 96 h post‐treatment, TIP concentrations were above the LOQ in one 8‐h sample (1.1 ppm) and two 24‐h samples (2.3 and 2.5 ppm). None of the 48‐h and 96‐h samples from these 4 studies contained measurable TIP concentrations. Thus, in cattle and pigs, only a small fraction of faecal samples collected up to 24 h postdosing contained measurable microbiologically active TIP, with its maximum limited to 2.6  μ g/mL. This is several log2 dilution steps below the MICs of TIP against foodborne pathogens and commensals collected under acidic conditions comparable with those in the colonic contents and may explain a lack of intestinal dysbacteriosis with parenteral tildipirosin in livestock.